Fish Production Technology of Small Scale Fish Farmers at Chaugachha Upazila under Jashore District of Bangladesh (Global Journal of Science Frontier Research, 2020)
The study was conducted on the fish farmer, which was situated at Chaugachha Upazila, Jashore, from October 2015 to April 2016. Data were collected using participatory rural appraisal (PRA) tools and personal observation. About 62% of the farmers have ponds of single, and 38% have multiple ownership. The homestead and commercial ponds were 79% and 21%, respectively. About 100% farmer carried out poly-culture fish farming though they did not know poly-culture just culture of various fishes. About 98% of the farmers control aquatic weeds manually. For controlling undesirable species, most of them (95.74%) used the netting method. Liming used 185.3-247 kg/ha and organic fertilizer, mainly cow dung used 741-1235 kg/ha. Average stocking density was found to be 12326 fry/ha. 91.5% of the farmers applied supplementary feed, such as both rice-bran and mustard oil-cake. The peak harvesting period was found from December to January. In this season, around 65% of the stocked fishes were reported to harvest, and the rest of the fish (35%) was harvested during another season.
Keywords: culture season; pre-stocking management; stocking density; fertilization; feed and feeding practices; fish production; harvesting and marketing